Exploring Sustainable Behaviour Among International Students: A Case Study of Waste Management in VOAS Housing - Niraula, Sharmila; Kapri, Swastika (My University, 2026)
The aim of this study is to explore sustainable waste management behaviour among International Student living in VOAS (Vaasa Student Housing Foundation) housing. The behaviour is examined by focusing on daily practices including waste sorting, and recycling behaviours. As most of the international students resides in student housing, understanding the factor shaping these behaviours are imperative for enhancing sustainable practices. The research of this study is based on two theories Theory of Planned Behaviour and the Value Belief Norm theory. These theories help to understand how individual perceived behaviour, social influences and personal norms influence their sustainable behaviours. To identify sustainable behaviour a quantitative research method was applied, and the data were collected through web survey. For the data collection, at first VOAS Housing were contacted through email after that survey questions were emailed to the respondent by VOAS from which 115 responses are received from international students residing in VOAS housing. The questionnaire was measured by formulating three hypothesis based on key factors including perceived behaviour control (H1), subjective norms(H2), personal norms(H3), and sustainable waste management behaviour (dependent variable). Demographics studies, descriptive statistics, reliability analysis, correlation and regression analysis were applied to identify the factors influencing sustainable behaviours. The findings shows that Personal Norm is the strongest factors of sustainable waste management behaviour, suggesting that international students who feel morally responsible for pro-environmental behaviour show consistent in sustainable behaviour. Perceived Behaviour Control also show significant factor that influenced sustainable behaviour, highlighting the importance of clear waste sorting guidelines, access to infrastructure facilities. Subjective norms did not significantly promote sustainable waste management among international students indicating that social expectations by peer pressure does not influence behaviour in VOAS housing. Practical recommendations are also mentioned to VOAS to focus on improving waste infrastructures, clear communication for waste sorting guidelines, and initiate community engagement programme.
Keywords: waste management; recycling; sustainable development; wastes; behaviour; social norms; norms; sorting of waste; case study; students; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business